The Analysis of the Structure for Testing and Evaluating Multiagent Systems with Autonomous Intelligent Agents - Bhatt, Mukul; Singh, Vaishali; Bhatnagar, Sanjay; V., Haripriya; Ahmed, Zahid (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Test and evaluation (T&E) ensure that created systems function as intended in anticipated and unforeseen circumstances. We look at the difficulties in developing a unified framework for testing and evaluating massive cyborg-like physical systems integrated artificial intelligence (AI). We provide a system incorporating testing and analysis into all development and operation phases to help the system learn and adapt in a loud, dynamic, and contested surroundings. The structure conserves testing time and resources when evaluating heterogeneous systems at various hierarchical composition sizes. For a general use case, the framework suggests potential research directions. Statistical modeling, Index systems engineering, AI, experimental design, software engineering (SE), and combinatorial interaction testing. This research proposes a deep learning system for CMF detection that uses CNN and CLAHE to classify photos as genuine or fake. Since some of the hidden elements of the picture are difficult to see using CMF, the CLAHE algorithm brings them to light.